2018
DOI: 10.5194/isprs-archives-xlii-3-1581-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Time Monitoring Service Platform for Land Supervision Based on Cloud Integration

Abstract: ABSTRACT:Remote sensing monitoring has become the important means for land and resources departments to strengthen supervision. Aiming at the problems of low monitoring frequency and poor data currency in current remote sensing monitoring, this paper researched and developed the cloud-integrated real-time monitoring service platform for land supervision which enhanced the monitoring frequency by acquiring the domestic satellite image data overall and accelerated the remote sensing image data processing efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One project, organized in response to a call by the Ministry of Lands and Resources issued to China's State Land Agencies, developed an early-warning and real-time monitoring platform for land supervision. In 2017, the Jinan Bureau of State Land Supervision piloted the platform, which "focus[ed] on the situation of illegal land use, permanent farmland protection and urban exploitation boundary breakthroughs in the supervision areas, and carried out real-time monitoring and early warning for all levels of land management departments to provide real-time image services" (Sun et al, 2018(Sun et al, : 1585. By the following year, the authors noted that the platform had processed 1400 satellite images in real time and had "truly achieved 'early warning, early detection and early deterrence'" (Sun et al, 2018(Sun et al, : 1585).…”
Section: Satellite State: Earth Observation For a Modern Governmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One project, organized in response to a call by the Ministry of Lands and Resources issued to China's State Land Agencies, developed an early-warning and real-time monitoring platform for land supervision. In 2017, the Jinan Bureau of State Land Supervision piloted the platform, which "focus[ed] on the situation of illegal land use, permanent farmland protection and urban exploitation boundary breakthroughs in the supervision areas, and carried out real-time monitoring and early warning for all levels of land management departments to provide real-time image services" (Sun et al, 2018(Sun et al, : 1585. By the following year, the authors noted that the platform had processed 1400 satellite images in real time and had "truly achieved 'early warning, early detection and early deterrence'" (Sun et al, 2018(Sun et al, : 1585).…”
Section: Satellite State: Earth Observation For a Modern Governmentmentioning
confidence: 99%
“…In 2017, the Jinan Bureau of State Land Supervision piloted the platform, which "focus[ed] on the situation of illegal land use, permanent farmland protection and urban exploitation boundary breakthroughs in the supervision areas, and carried out real-time monitoring and early warning for all levels of land management departments to provide real-time image services" (Sun et al, 2018(Sun et al, : 1585. By the following year, the authors noted that the platform had processed 1400 satellite images in real time and had "truly achieved 'early warning, early detection and early deterrence'" (Sun et al, 2018(Sun et al, : 1585). An article by two scientists from the Surveying and Mapping Institute of the Lands and Resource Department of Guangdong Province similarly used GF data for land use enforcement.…”
Section: Satellite State: Earth Observation For a Modern Governmentmentioning
confidence: 99%
“…The Guizhou Plateau Lake, located in the Karst region, has a shallow soil layer and a weak water-holding capacity leading to a number of environmental problems such as frequent shortage of surface water, fragile ecology, and rapid diffusion of pollutants [23]. Comparing the water environment conditions in typical lakes in China, researchers reported that nitrogen and phosphorus are far more concentrated in Guizhou Plateau Lake than in other lakes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%